MODAL SOSIAL DAN KEBERDAYAAN KELOMPOKTANI PADI DI KECAMATAN BUNGA RAYAKABUPATEN SIAK - Muhamad Raisman; Roza Yulida; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to : 1) identify social capital of the farmers group of rice in Siak District. 2) identify empowerment of the farmers group of rice in Siak district. 3) identify the correlation between social capital and empowerment of the farmers group of paddy in Siak district. This research used survey method with the number of respondents is 63 farmers who join to the farmers group of rice purposively selected. In identifying social capital and empowerment, the researcher used qualitative desciptive method, while to identify the correlation between social capital and empowerment, the researcher used graphic percentage method. The result of the research showed that : 1) the implementation of social capital to the medium farmers group of rice was better than those in advanced group due to all elements of social capital were handled well by medium group. 2) the empowerment of medium farmers group of rice was higher than advanced group. 3) the percentage of social capital of advanced group was 52.63% followed by empowerment 58.33%. While the perentage of social capital of medium group was 89.47% followed by empowerment 100%.Keywords : Social Capability, Empowerment, farmersGroup, Correlation